Neglected, Drug-Induced Platinum Accumulation Causes Immune Toxicity - Zhang, Yuling (Front Pharmacol, 2020)
Previous studies only focused on different adverse reactions caused by various platinum drugs, but not on common immunotoxicity caused by the accumulation of elemental platinum. Here, we determined the serum platinum concentrations of cancer patients after a metabolism period of platinum drug chemotherapy, in addition to hematological indices and subsequent immune-related adverse reactions, then analyzed the correlations between platinum accumulation, immune cell levels, and immune-toxicity. We chose the day before the next round of chemotherapy as the specified time point for blood sampling. Samples were collected at five time points, separately in oxaliplatin and cisplatin groups. The median serum platinum concentrations in all patients was 294.8 (205.6, 440.3) μg/L, and was approximately two-fold greater in the cisplatin group than in the oxaliplatin group (429.3 vs. 211.7 μg/L). The platinum level of both groups peaked at the third time point, with the average of females being higher than males (383.9 vs. 266.5 μg/L), and was positively correlated with leukocyte and platelet counts, but negatively correlated with erythrocyte counts and concentration of hemoglobin. The risks of anemia and adverse reactions were individually increased by 0.002- and 0.007-fold for every μg/L increase of platinum concentration. To our knowledge, this is the first study on the relationship between platinum accumulation, immune cell levels and toxicity, showing that drug-induced platinum accumulation may interfere with immune cells and thus increase the risk of toxicity.